2020
DOI: 10.2147/ijwh.s234408
|View full text |Cite
|
Sign up to set email alerts
|

<p>Glycosylated Hemoglobin A1c Is Associated with Anthropometric Measurements and Tumor Characteristics in Breast Cancer Patients</p>

Abstract: Purpose: To investigate the association between glycosylated hemoglobin A1c (HbA1c) with anthropometric measurements and clinicopathologic characteristics of breast cancer patients. Such data are lacking in Arabian countries. Patients and Methods: A cross-sectional study was conducted at the Outpatient Oncology Unit at King Hussein Medical Center at the Royal Medical Services (RMS) and 223 breast cancer patients were included. Blood levels of HbA1c were measured and patients were classified into normal/non-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Apart from the associations with overall reduced physical health, significant associations were found for elevated plasma C-reactive protein and glycosylated hemoglobin HbA1c levels in breast cancer survivors [ 112 ]. Both have been previously identified as potential risk factors associated with cancer recurrence and comorbidities in breast cancer survivors [ 113 , 114 ]. Our own research concerning DAL in breast cancer survivors did not include disease-specific endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the associations with overall reduced physical health, significant associations were found for elevated plasma C-reactive protein and glycosylated hemoglobin HbA1c levels in breast cancer survivors [ 112 ]. Both have been previously identified as potential risk factors associated with cancer recurrence and comorbidities in breast cancer survivors [ 113 , 114 ]. Our own research concerning DAL in breast cancer survivors did not include disease-specific endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer, the most frequent cancer in women, is a major public health issue. Several studies have provided strong evidence for a positive association between obesity, diabetes/IGT, and increased risk of breast cancer development as well as recurrent metastasis [30][31][32][33][34][35][36]. The combined effect of obesity and diabetes on breast cancer outcomes has been extensively reported in humans [21][22][23]37], and undiagnosed IGT is known to affect the survival of breast cancer patients [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wu et al also reported associations between DAL and elevated plasma CRP and HbA1c levels in breast cancer survivors [ 29 ]. Both are important risk factors associated with cancer recurrence and comorbidities in in this particular group [ 62 , 63 ]. A high DAL may contribute to systemic inflammation and hyperglycemia in cancer survivors [ 29 ], which, in turn, has been associated with a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%